The Study of Effectiveness of Auditory, Language and Speech Rehabilitation and Correlating Factors in Children with Cochlear Implantation from 4 Regions - Ruamsuk, Somjit; Thanasriseabwong, Pornpat; Kaewsiri, Suwicha; Atchariyasathian, Viraporn (Journal Of Ratchasuda Institute for Research and Development of Persons With Disabilities, 2023)
This research aimed (1) to study on results from hearing, speech and language rehabilitation in children who receive Cochlear Implant (CI), (2) to study factors that may affect rehabilitative capacities, and (3) to determine the minimum average number of sessions required to improve skills. Researchers had screened children who would be suitable for CI and rehabilitation that consisted of 13 children aged 1-4 years. After the operation, all children received rehabilitation one session per week, with 30-60 minutes per session for the duration of 2 years. Speech and language evaluation were conducted 6 times, with one evaluation prior to the operation, and the remaining 5 sessions in post-operation consisted of 1, 3, 6, 12, 24 months after the first rehabilitative session, using assessment for pre-post CI and the first 100 vocabulary checklist, Ling Six Sound Test and CAP scales and Articulation test. Statistical analysis will be analyzed via descriptive, One-way Repeated Measure ANOVA and Multiple Regression. Overall average scores of listening, language and speech clarity (articulation) assessment from CI candidates in 1, 3, 6, 12, 24 months post-operation, 17.9±11.6, 27.7±13.4, 37.2±14.2, 55.3±26.7 and 109.3±82.7, have higher average scores than pre-operation 6.3±9.0 in all ranges with statistical significance (p<0.05). The most prominent factor in average assessment scores is the age, with the average 19.0 scores increased after 1 year of rehabilitation and require at least 4 sessions within a month to improve skills. In conclusion, the screening, operation, and rehabilitation protocols in children who receive CI in this study can be used as the effective model for the screening, operation, hearing skills and speech and language rehabilitation protocols for children with hearing impairment in Thailand, since they are able to cover all important aspects in communication, and also determine the prominent factor to the rehabilitation. It is evident that all candidates yield improved skills and also encourage the multidisciplinary approach and, most importantly, the parents.